Effects of spin coating parameters on stress, electrical and optical properties of multilayer ZnO thin film prepared by sol-gel - Demircan, Gokhan; Gurses, Enes Furkan; Acikgoz, Abuzer; Yalcin, Serife; Aktas, Bulent (Molecular Crystals and Liquid Crystals, 2020)
In this study, zinc oxide (ZnO) thin films deposited on to glass substrates have been manufactured by sol-gel spin coating method at various spin speed and time. The effect of spin speed and time on film thickness, structural properties, and residual stress parameters has been investigated. Scanning electron microscope investigations have shown that the thickness of films has changed depending on coating parameters. X-ray diffraction measurements have indicated that polycrystalline films have formed with hexagonal wurtzite structure on the sample surfaces. The values of residual stress on the ZnO film have enhanced with increasing coating speed and also decreased with increasing film thickness. The UV transmittance of the prepared thin films has changed between 70% and 95% depending on the coating speed and time. The fluorescence measurements of the thin films have been determined in the spectral range from 350 nm to 900 nm. It has been observed that the fluorescent intensity has a high value in 2000 rpm-50 s. Furthermore, the electrical conductivities of the ZnO films have increased by diminishing the film thickness.